Intergenerational solidarity from a generation Z perspective - Šećerov Milena; Solarević Milica (Glasnik Srpskog Geografskog Društva, 2025)
Acknowledging that the 21st century is characterized by a significant rise in life expectancy and a growing aging population, this societal shift has become a central focus in numerous public policies. The focus of this article is to delve into the attitudes of Generation Z concerning intergenerational connection and solidarity, particularly towards older adults. The primary objective of this paper is to analyze society's readiness for intergenerational solidarity and mutual respect, with a keen awareness of the obstacles that may hinder such progress, focusing on older adults and Generation Z. The research is based on a questionnaire on the attitudes of Generation Z about intergenerational solidarity towards older adults. Results indicate that Generation Z currently spends limited time with older adults but has a legitimate desire to spend more time with older adults. Moreover, this generation deeply respects older adults, recognizing their vital role as integral links in our society. They are committed to providing love and support to older adults while valuing the wealth of experience they can learn from.